A representação social de jovens batistas do subúrbio ferroviário de Salvador : reflexão para uma teologia do cuidado entre jovens evangélicos estigmatizados e em situação de vulnerabilidade psicossocial - Souza, Robson (2008)
This research aimed to ascertain the extent to which factors such as stigmatization, discrimination, social determinism, situation of vulnerability psychosocial, faith, image of God and relationship with God influence the way the social representation of youngs Igreja Batista Central from Paripe. Subjects in situations of social exclusion, in this speech, more specifically, trying to understand the relationship that young people have with the standards of the church and faith in God, and identify the association between these structures with self-esteem of young people in question.